PENGEMBANGAN MEDIA POP UP BOOK PANDRA (PANCA INDRA) MENGGUNAKAN MODEL CTL (CONTEXTUAL TEACHING AND LEARNING) PADA MATERI MENGENAL ANGGOTA TUBUH KEIAS 1 - Abibatun Nuraini Sa'diyah (JUSEDA, 2022)
This research is motivated by teachers who rarely use learning media, especially on body parts material. This study aims to produce Pop Up Book media on the Material Knowing the Members of the Body CIass I. The method used in this research is the ADDIE development modeI, which incIudes analisys, design, development, implementation and evaluation. The subjects in this study were 3 expert validators. The results of the development of this Pop Up Book meet the standards of validity of the expert validators. The final score of the material expert validation got a score of 95.31% with the "very valid" category and the final score of the media expert validation got a score of 95.8% in the "very valid" category. So it can be concluded that the PANDRA Pop Up Book (The five sences) media can be used for learning process activities.